2009
DOI: 10.1002/ejoc.200900407
|View full text |Cite
|
Sign up to set email alerts
|

Towards Long‐Living Metathesis Catalysts by Tuning the N‐Heterocyclic Carbene (NHC) Ligand on Trifluoroacetamide‐Activated Boomerang Ru Complexes

Abstract: The synthesis and characterization of three novel trifluoromethylamido-containing "boomerang" precatalysts bearing various N-heterocyclic carbene (NHC) ligands are reported. Comparative kinetic and stability studies show the significant effect of the NHC on the catalyst reaction profile. An investigation of the reaction scope for diverse metathesis transformations has allowed us to establish the influence of the NHC on catalyst activity, especially as a function of substrate steric bulk. The excellent stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 66 publications
1
40
0
4
Order By: Relevance
“…Without any pre-treatment,u pt o0 .05 mol %( 500 ppm) of Ru-6a was needed to convert 89 %o f( Z)-1 within 15 min at 50 8C under neat condition and to reach the equilibrium [Eq. This result clearly demonstrated that, despite the robustness and high stabilityo ft he M71p re-catalyst, [13] the presence of certains ubstrate impurities has ad ramatic effect on catalyst efficiency.T herefore, witht he objective to reach an optimal catalytic process, it appeared important to us to clearly identify these poisons and to adapt accordingly.A large variety of organic molecules can be found in vegetal oils ( Figure 2). [15] As ignificant amount of methyl elaidate (E)-1 was also formed (41 wt %, see SupportingI nformation for details).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Without any pre-treatment,u pt o0 .05 mol %( 500 ppm) of Ru-6a was needed to convert 89 %o f( Z)-1 within 15 min at 50 8C under neat condition and to reach the equilibrium [Eq. This result clearly demonstrated that, despite the robustness and high stabilityo ft he M71p re-catalyst, [13] the presence of certains ubstrate impurities has ad ramatic effect on catalyst efficiency.T herefore, witht he objective to reach an optimal catalytic process, it appeared important to us to clearly identify these poisons and to adapt accordingly.A large variety of organic molecules can be found in vegetal oils ( Figure 2). [15] As ignificant amount of methyl elaidate (E)-1 was also formed (41 wt %, see SupportingI nformation for details).…”
mentioning
confidence: 77%
“…It is also important to note that below ac atalystl oading of 400 ppm, no reactivity was observed. This result clearly demonstrated that, despite the robustness and high stabilityo ft he M71p re-catalyst, [13] the presence of certains ubstrate impurities has ad ramatic effect on catalyst efficiency.T herefore, witht he objective to reach an optimal catalytic process, it appeared important to us to clearly identify these poisons and to adapt accordingly.A large variety of organic molecules can be found in vegetal oils ( Figure 2). Some are naturally present (Np1-3), some are formed during the hydrolysis (Hp1-2)o rd uring the esterification process (Ep1-3)t op roduce fatty acid/esters, and some result from decomposition by oxidation and/orp olymerization (Dp1-3).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…However, as these catalysts are vastly employed as homogeneous systems, removal of the metallic species from the metathesis products, especially in the case of pharmaceuticals, is quite a tedious procedure. Though various means such as the use of scavenger materials, chromatographic purification protocols, and oxidative processes are being practised, such steps substantially add to the overall process cost as well as to the environmental concerns . As an alternative approach, it has been recommended to heterogenize the Grubbs/Hoveyda‐Grubbs catalysts and hence easily recover/reuse the ruthenium‐carbene complexes .…”
Section: Metal‐alkylidene Based Heterogeneous Catalyst Systemsmentioning
confidence: 99%
“…ee Reactions involving C-H activation of aromatic and aliphatic bonds by iridium complexes have been jointly studied by both experiment and computation; 99 a route involving intermediate hydride carbene complexes has been identified as one of two competitive pathways. Sulfoxonium ylides (60) have been successfully used as safe and practical surrogates of diazo compounds for X-H insertion catalysed by iridium complexes leading to α-functionalized carbonyls (61). 100 A lactam ring-expansion process has nicely illustrated the usefulness of this method.…”
Section: Transition Metal-assisted Reactionsmentioning
confidence: 99%